Integral Role of GDF-9 and BMP-15 in Ovarian Function - Otsuka, Fumio (2011)
The oocyte plays an important role in regulating and promoting follicle growth, and thereby its own development, by the production of oocyte growth factors that predominantly act on supporting granulosa cells via paracrine signaling. Genetic studies in mice demonstrated critical roles of two key oocyte-derived growth factors belonging to the transforming growth factor-β (TGF-β) superfamily, growth and differentiation factor-9 (GDF-9) and bone morphogenetic protein-15 (BMP-15) in ovarian function. The identification of Bmp15 and Gdf9 gene mutations as the causal mechanism underlying the highly prolific or infertile nature of several sheep strains in a dosage-sensitive manner also highlighted the crucial role these two genes play in ovarian function. Similarly, large numbers of mutations in the GDF9 and BMP15 genes have been identified in women with premature ovarian failure and in mothers of dizygotic twins. The purpose of this article is to review the genetic studies of GDF-9 and BMP-15 mutations identified in women and sheep as well as describing the various knockout and over-expressing mouse models, and to summarize the molecular and biological functions that underlie the crucial role of these two oocyte factors in female fertility.